Rhinitis and its impact on quality of life in swimmers. Issue 5 (19th December 2017) - Surda, P.; Putala, M.; Siarnik, P.; Walker, A.; Bernic, A.; Fokkens, W.
Abstract: Introduction: Limited data suggest that swimmers might be affected by rhinitis significantly more often than the general population. This can have impact on quality of life but also on performance. The aim of this study was to determine the prevalence and impact of QOL of rhinitis in swimming compared to nonswimming athletes and controls. Materials and methods: This was an observational case‐control, questionnaire‐based study involving elite (n = 101) and nonelite swimming athletes (n = 107), nonswimming athletes (n = 38) and sex‐ and age‐matched controls (n = 50). The survey instrument consisted of a general and the miniRQLQ. Main question used to assess the prevalence of rhinitis was from the ISAAC study. Results: Rhinitis was reported significantly more often by the elite swimmers (45%) than nonelite swimmers (31%), nonswimming athletes (32%) and controls (24%). Allergic rhinitis prevalence was similar in all groups (12%‐18%). The prevalence of nonallergic rhinitis (NAR) was significantly higher in elite swimmers (33%) and nonelite swimmers (22%) compared to nonswimming athletes and controls. Overall mean miniRQLQ score and all subdomains except the "eye" domain showed significantly reduced QOL in elite and nonelite swimmers compared to nonswimming athletes and controls. Regular nasal medication was used significantly less by elite swimmers (18%) compared to controls (67%) and nonswimming athletes (42%). Conclusion: This study revealed a high prevalence of NAR in swimmers and related impact on QoL. These findings highlight the importance to increase the awareness towards upper airway disorders in the swimming athletes and to ensure adequate management.